Mechanical Pain Thresholds and the Rubber Hand Illusion - Bauer, Anna; Hagenburger, Julia; Plank, Tina; Busch, Volker; Greenlee, Mark W. (Frontiers in Psychology, 2018)
We manipulated the sense of body ownership with the Rubber Hand Illusion (RHI) to determine if perception of a potentially painful threat to the rubber hand can modify the mechanical pain threshold (MPT). Simultaneous tactile stimulation of the subject’s concealed hand and the appropriately positioned visible rubber hand generated the illusion of false body ownership. The MPT was recorded on the left hand of the subjects before and after induction of the RHI, as well as during the phase in which the model hand was pricked with a sharp knife or touched by the blunt knife handle. The results indicate that the RHI could be successfully generated with our set-up. Mechanical stimuli were perceived as more painful in the condition where the rubber hand was simultaneously pricked with a knife. Our findings suggest that the illusion of body ownership gates nociceptive processing of potentially painful stimuli.